Interdiscursive analysis of corporate environmental reports of oil and gas companies in Malaysia / Aliyyah Nuha Faiqah Azman Firdaus - Aliyyah Nuha Faiqah, Azman Firdaus (2016)
Over the last 20 years, research on corporate environmental reporting (CER) has been largely monopolised by the accounting, business and engineering disciplines. The surge in the publication of such reports has led to differing interpretations of the contents depending on the different needs and interests of the stakeholder community. Although many studies have been carried out in the past, very few have examined this genre from a linguistic perspective. An in-depth study on the discourses of CER may uncover novel insights that would contribute to its existing literature. Therefore, this study investigates the practice of environmental disclosure of five Malaysian oil and gas companies by using Bhatia’s (2004) multidimensional framework for genre analysis. It examines the underlying communicative purposes and private intentions, which are discursively constructed by the corporate community. The methods used in this study include textual analysis of the reports and a semi-structured interview with a former corporate environmental report writer. Discursive strategies that are employed within this genre are discussed in relation to the rhetorical and linguistic features found in these reports. Findings show that there are multiple overlapping discourses that are strategically combined and appropriated within the discursive space of CER to realise specific communicative purposes and private intentions of these corporations. These include the discourses of accountability, discourses of compliance, discourses of promotion and discourses of self-justification. The prevalence of interdiscursivity in CER may be related to the nature of business and the function of corporate communication in oil companies.